The Ecosystem of AI-Driven Robotics in Pediatric Neurorehabilitation - Sutikno, Tole; Handayani, Lina (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2025)
If you want to fully understand the ecosystem surrounding AI-driven robotics in pediatric neurorehabilitation, you need to carefully look at many interconnected aspects and think critically about what they mean. We address this review to facilitate an in-depth analysis of the effective integration of advanced technologies, such as artificial emotional intelligence and interactive reinforcement learning, into rehabilitation practices. By critically assessing each element, from the psychological dynamics of patient engagement to the technical intricacies of real-time adaptive learning systems, we can better understand their pivotal roles in enhancing therapeutic efficacy. Moreover, the inclusion of natural language processing and facial expression analysis warrants careful consideration, as it sets the stage for more nuanced interactions between robots and pediatric patients, thereby fostering a therapeutic environment that is both responsive and empathetic. A thorough examination not only highlights the potential benefits but also the ethical and practical challenges associated with these technologies. By putting these different parts into a critical framework, we ensure that we have a complete picture of the opportunities and limitations in this new field. Our ultimate goal is to improve rehabilitation outcomes for kids with neurological problems while keeping an eye out for any unintended effects.